Пушкин в кругу современников = Pushkin among his contemporaries - Leibov, Roman; Okhotin, Nikita (Acta Slavica Estonica, 2019)
Acta Slavica Estonica is an international series of publications on current issues of Russian and other Slavic languages, literatures and cultures. This volume continues the long tradition of Tartu Pushkin studies, which began in the 19th century, but became truly influential in the era when Yu. M. Lotman headed the Department of Russian Literature. This tradition has continued over the past decades. The volume includes contributions by scholars from St. Petersburg, Moscow, Tartu, Oxford, Madison, Milwaukee. There are commentaries on specific texts of Pushkin, as well as general observations on the literary processes of the early 19th century.